OXIDATIVE STRESS AND ORAL HEALTH IN PEDIATRIC TYPE 1 DIABETES: A COMPARATIVE STUDY OF ANTIOXIDANT ENZYME ACTIVITY AND LIPID PEROXIDATION MARKERS - Amelia Surdu; Daniela Trifan; Irina-Georgeta Sufaru; Oana Cristina Cretu; Mihaela Monica Scutariu (Romanian Journal of Oral Rehabilitation, 2024)
Objectives: This study investigates the relationship between Type 1 diabetes mellitus (T1DM) and periodontal health in pediatric patients, focusing on oxidative stress markers and antioxidant enzyme activity. T1DM in children is associated with elevated levels of oxidative stress, which exacerbates inflammatory responses and increases susceptibility to periodontal disease. Materials and methods: In this observational study, clinical periodontal parameters, such as Plaque Index (PI), Bleeding on Probing (BOP), Probing Depth (PD), and Clinical Attachment Loss (CAL), were compared between two groups: healthy children and children with T1DM. Additionally, plasma malondialdehyde (MDA), superoxide dismutase (SOD), and glutathione peroxidase (GPx) levels were assessed to evaluate oxidative stress and antioxidant capacity. Results and Discussion: Results indicated significantly higher BOP, PD, and CAL in the T1DM group, highlighting an elevated risk of periodontal disease. Paraclinical findings also showed increased MDA and reduced SOD and GPx activity in the T1DM group, suggesting compromised antioxidant defenses. Conclusions: This study emphasizes the need for integrated periodontal and systemic oxidative stress management in pediatric T1DM to mitigate complications and improve health outcomes.